If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2w + -9(6 + -10w) = 29 + 5w -2w + (6 * -9 + -10w * -9) = 29 + 5w -2w + (-54 + 90w) = 29 + 5w Reorder the terms: -54 + -2w + 90w = 29 + 5w Combine like terms: -2w + 90w = 88w -54 + 88w = 29 + 5w Solving -54 + 88w = 29 + 5w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-5w' to each side of the equation. -54 + 88w + -5w = 29 + 5w + -5w Combine like terms: 88w + -5w = 83w -54 + 83w = 29 + 5w + -5w Combine like terms: 5w + -5w = 0 -54 + 83w = 29 + 0 -54 + 83w = 29 Add '54' to each side of the equation. -54 + 54 + 83w = 29 + 54 Combine like terms: -54 + 54 = 0 0 + 83w = 29 + 54 83w = 29 + 54 Combine like terms: 29 + 54 = 83 83w = 83 Divide each side by '83'. w = 1 Simplifying w = 1
| 10x-10=5x-2 | | 7x^4-13x^2-15= | | 6+2(9+4x)=5x+3 | | x^3-4x^2-11x=-30 | | BD=2(a+1) | | 3+4ab-9b^2= | | 3(x+2.64)=2x | | AC=2(5a+1) | | 600x-0.34=100x+0.81 | | -2x+10=10y | | 1.1x+2-4.1x=8 | | X+2/2=10-x+2/3 | | -3x+y=-17 | | 5x-32.4=x | | 0.4x+0.9=-1.1 | | 18-7x=2x | | 2/9r+10=-10 | | 6(2-t)-(4-4t)=5 | | 4(3-t)-(2-2t)=7 | | 9.8+x/5=10.4 | | 7x=5y | | y(3y+8)=-5 | | (r/-7)-5=-6 | | 3x+4=(x-8) | | 2y+8=10y | | w^2-14w-72=0 | | c=5(F-32)/9 | | 60x^2-44x-5= | | -24+6=-5 | | -10x-3x-3x=-70 | | (3x-6)(5x-9)= | | 3x/4-1 |